Mempertanyakan Nilai Keadilan Sosial Dalam Pembangunan Ekonomi di Tengah Kekuatan Modal - Hendrikus Tri Wibawanto Gedeona (Centre for Public Policy and Management Studies, 2004)
Economic development that should be a manifest of concern and responsibility of government for public needs and fairly nation development had been marginalized by pro-capital economic development policy. The policy formulation have neglected the social justice value that should be the supreme virtue of the good state. The government orientation to protect the most substantive public needs in fairly and democratic way as basic prerequisite needed for rearrangement of social justice economic development.Kata kunci : pembangunan ekonomi, nilai keadilan sosial, kepentingan modal, dan pemerintah yang demokratis.